2022
DOI: 10.1093/neuonc/noac032
|View full text |Cite
|
Sign up to set email alerts
|

The impact of brain invasion criteria on the incidence and distribution of WHO grade 1, 2, and 3 meningiomas

Abstract: Background In 2016, brain invasion was added as a standalone diagnostic criterion for Grade 2 meningiomas in the WHO Classification of Brain Tumors. The aim of this study was to compare the incidence and distribution of meningiomas, and agreement, between the 2007 and 2016 WHO criteria. Methods All cases of intracranial meningiomas diagnosed between 2007 and 2020 at a tertiary care academic hospital were identified. The incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…With the advent of CNS invasion as a stand-alone criterion for atypia in the WHO classification since 2016, an unusual increase in cases with histopathological CNS invasion was observed, presumably based on a tendency of some pathologists to assign a higher grade when in doubt ( Perry, 2021 ). On the other hand, a larger retrospective study of 814 meningiomas showed only a slight non-significant increase of WHO 2 meningiomas after the inclusion of CNS invasion in the WHO classification ( Rebchuk et al., 2022 ). Therefore, a varying adherence to the criteria of CNS invasion proclaimed by the recent WHO classification can be suspected, although they have been defined quite clearly, with pial breach and protrusion of meningioma tissue into GFAP-positive tissue as proof of invasive growth.…”
Section: Discussionmentioning
confidence: 96%
“…With the advent of CNS invasion as a stand-alone criterion for atypia in the WHO classification since 2016, an unusual increase in cases with histopathological CNS invasion was observed, presumably based on a tendency of some pathologists to assign a higher grade when in doubt ( Perry, 2021 ). On the other hand, a larger retrospective study of 814 meningiomas showed only a slight non-significant increase of WHO 2 meningiomas after the inclusion of CNS invasion in the WHO classification ( Rebchuk et al., 2022 ). Therefore, a varying adherence to the criteria of CNS invasion proclaimed by the recent WHO classification can be suspected, although they have been defined quite clearly, with pial breach and protrusion of meningioma tissue into GFAP-positive tissue as proof of invasive growth.…”
Section: Discussionmentioning
confidence: 96%
“…The reason for this is that the new, revised criteria include BI as an independent, histological criterion for diagnosing AM. Formerly WHO grade 1 meningioma patients were included as having AM once the new BI-based criterion was applied to them, resulting in an increase of 1–10% in the incidence of AM [ 23 , 34 ], as well as an increase in the proportion of BI in AM. In terms of clinical risk factors for BI in AM, our study found that patient sex, age, tumor location, and V Tumor were not involved, consistent with the findings of several studies [ 8 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meningiomas are the most common primary central nervous system tumors in adults (1,2), accounting for 39.0% of all intracranial tumors (3). They are divided into three grades and 15 subtypes according to the 2021 World Health Organization (WHO) Central Nervous System (CNS) tumor classification (3).…”
Section: Introductionmentioning
confidence: 99%